Analisis Korelasi Stigmatisasi dengan Kecemasan pada Penderita Tuberkulosis yang Sedang Menjalani Pengobatan (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the relationship between stigmatization and the level of anxiety felt by tuberculosis patients undergoing treatment in the Kassi-Kassi Community Health Center working area in Makassar City. The study used a quantitative correlation research method with a Cross Sectional Study approach and used the Spearman test. The results of this study showed p Value = 0.000 (p